An assessment of the effects of simulation training on management of postpartum hemorrhage: short- and long-term impact on knowledge retention, skills and teamwork in the Democratic Republic of Congo - Jean Paul Buhendwa Cikwanine; Denis Mukwege; Justin Mongwa; Emile Mapatano shalamba; Raha Maroyi; Jonathan Tunangoya Yoyu; Ludovic Martin (BMC Medical Education)
Abstract Background Major obstetric hemorrhage is the leading direct cause of maternal mortality throughout the world. To prevent maternal mortality, it is crucial to raise concerns regarding the knowledge and skill levels of the healthcare providers. The purpose of this study was to investigate the impact of simulation-based learning on the knowledge retention and skills of health professionals managing postpartum hemorrhage (PPH) in the maternity hospitals of a low-resource country. Methods This was a prospective randomized controlled study consisting of two groups: Control Group was made up of maternity hospital healthcare providers whose training was exclusively theory-based and Intervention Group healthcare providers who underwent simulation training in conjunction with theoretical instruction on diagnosing and managing PPH. The training modules were taken from the John Hopkins University Affiliate (JHPIEGO) Helping Mothers Survive version 2018 training program. The mean percentage of correct answers in MCQs and OSCEs was collected from pre-tests, immediate post-tests, and post-tests at 3- and 6-months post training. Results The post-test immediately after the theoretical training showed an increase in the mean MCQ percentages for both groups. From 47.5 to 66.7% for intervention group versus 49.6–69.6% for control group; no significant difference between the two groups (p = 0.285). After simulation training, for the interventional group, the mean percentage increased from 66.7 to 79.2%, an increase of approximately 12%. There was a regression in the mean percentage in both groups in the post-test at 3- and 6-months after the training, but it was much more pronounced in the control group, p = 0.000. OSCE assessments revealed a statistically significant improvement in skills in interventional group compared to control group (p < 0.05). Knowledge and skills diminished over time in control group, bordering on pre-training levels at 6 months post training. The member team in the intervention group had maintained a high level of knowledge and skill 6 months after the training. Conclusion Simulation-based training has a part to play in training healthcare providers to manage post-partum hemorrhage. Training should be repeated after a period of 6 months to enhance knowledge and skill retention. Trial registration NCT05979701.